Development of Apple Juice Beverage Industry In Batu City Through Marketing Intelligence And Strategic Alliances Approach - Mas’ud Effendi; Siti Asmaul Mustaniroh; Febrina Grace Tri Anti; Arifianto Hidayat (APTA and DTIP FTP UGM, 2017)
The existence of apple juice industry in Batu is dominated by micro, small and medium enterprises (SMEs). This industry needs to be developed to direct the Batu potential as a tourism city through the development of agro-industry sector, which delivers added value. The purpose of this study to find out the source of the information, the type of information in the apple juice industry ingeneral and alliances form in the apple juice industry on micro and small scale that can be used for the development of the apple juice industry in Batu city. The results showed that the most important source of information and always used by the apple juice industry in Batu city is talking to customers with the strengths and weaknesses of competitors, cash flow, and corporate realgrowth as the most important type of information. Alliances that may be made to the development of micro and small-scale apple juice beverage industry with distributors are type of logisticsalliance, promotion alliance, and non-equity alliances.